Engineering the risks of hazardous wastes - Vallero, Daniel A. (Butterworth-Heinemann, 2003)
Many engineers, from the chemical and process industries, waste treatment system management and design to the clean-up of contaminated sites, are engaged in careers that address hazardous wastes. However, no single book is available that explains how to manage the risks of those wastes. At best it is dealt with in diverse sections of books on the general field of environmental engineering, and in various treatments of the subject of risk, statistics and hazard assessment. This is a reference and text that blends together theoretical explanations, techniques and case study examples to complement practical knowledge. These include problems with solutions, case studies of current and landmark hazardous waste problems, a companion website, and reference sections that will make certain that this text stays on the practicing engineer's bookshelf. - Addresses a subject of theoretical and regulatory importance - The only book to take this approach - Includes textbook case studies and examples as well as practical advice.
Keywords: Hazardous wastes -- Risk assessment.; elektronické knihy; electronic books